GENERALIZED POST-VACCINAL COMPLICATION AFTER BCG REVACCINATION. SKIN AND HYPODERMIC TUBERCULOSIS, CICATRIZATION STAGE. CASE STUDY - E. I. Pilguy; A. K. Gevorkyan; Y. V. Rovenskaya; L. K. Aslamazyan (Педиатрическая фармакология, 2013)
The article presents a case of a rare post-vaccinal complication, which appeared after BCG revaccination in the setting of insignificant catarrhal phenomena in a girl of 7 years 6 months of age. An ulcerous defect started to form on the 2nd-3rd day on the vaccine administration site. Similar ulcerous lesions started to form on facial skin on sites of cat scratches within the first week. Later, the ulceration spread on all cutaneous coverings. Multiple deep drawn-in cicatrical defects remained on the girl’s skin after long-term treatment at various inpatient hospitals. The developed generalization of the infectious process may have resulted not only from violating the vaccination technique, but also from untimely diagnostics and incorrect disease treatment tactics. The article throws light upon clinical forms and differential diagnostics of various skin tuberculosis forms and presents modern tuberculosis vaccinal prevention issues, classification and causes of post-vaccinal complications.